1996
DOI: 10.1093/carcin/17.10.2267
|View full text |Cite
|
Sign up to set email alerts
|

SHORT COMMUNICATION: Influence of a mutation reducing the catalytic activity of the cytochrome P450 CYP2D6 on lung cancer susceptibility

Abstract: The possible association between lung cancer and the CYP2D6*9 mutant allele, which reduces the catalytic activity of cytochrome P450 CYP2D6, was examined by PCR-SSCP using peripheral blood DNA from 249 cases of lung cancer and 265 controls, with detailed data on smoking. The CYP2D6*9 mutant allele was present in 4.9% of controls and 6% of cases. Adjusted for age, hospital and smoking, the odds ratio (OR) of lung cancer associated with the presence of the CYP2D6*9 mutant allele was 1.2 [95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the case of CYP2A6 and CYP2D6, the altered base causes a reduction in enzyme function (22,23). On the contrary, the variant form of the protein causes the enhanced activity of CYP1A1 and CYP1B1 enzymes (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CYP2A6 and CYP2D6, the altered base causes a reduction in enzyme function (22,23). On the contrary, the variant form of the protein causes the enhanced activity of CYP1A1 and CYP1B1 enzymes (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms and mutations in genes cause changes in the function of proteins, which can reduce [27][28][29] or enhance [30][31][32] the activation of enzymes. Polymorphisms of various genes have also been shown to be associated with cancers [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Although the first association between CYP2D6 enzyme activity and lung cancer risk was described in 1984, the role of CYP2D6 in lung cancer risk is still a controversial topic (Ayesh, Idle, Ritchie, Crothers, & Hetzel, 1984). Although most studies failed to identify a significant association, some studies reported a minor positive association (Agundez et al, 2001;Legrand et al, 1996;London et al, 1997). The overall results indicated a modest association of CYP2D6 polymorphism with lung cancer risk.…”
Section: Cyp2d Subfamilymentioning
confidence: 99%